2015
DOI: 10.1016/j.jedc.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Labor supply and the optimality of Social Security

Abstract: Traditional economic theory predicts that unfunded social security can be justified on the basis of its ability to efficiently finance retirement, and also for its ability to provide insurance against mortality risk and uninsurable shocks to labor income. In this paper, I demonstrate that the quantitative importance of the traditional roles of social security depends on how household labor supply responds to social security. I build a calibrated general-equilibrium model where social security has a large welfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…The fact that eliminating the cap on Social Security taxes and benefits reduces overall welfare should not be surprising. In a general-equilibrium model with endogenous labor, the distortionary effects of Social Security on labor supply are often large enough to outweigh the welfare gains from its insurance effects (Nishiyama and Smetters, 2008;Bagchi, 2015). I report in Table 9 the consumption equivalence (ψ) for each value of the permanent productivity shock under Case 1.…”
Section: Two Experiments With the Capmentioning
confidence: 99%
“…The fact that eliminating the cap on Social Security taxes and benefits reduces overall welfare should not be surprising. In a general-equilibrium model with endogenous labor, the distortionary effects of Social Security on labor supply are often large enough to outweigh the welfare gains from its insurance effects (Nishiyama and Smetters, 2008;Bagchi, 2015). I report in Table 9 the consumption equivalence (ψ) for each value of the permanent productivity shock under Case 1.…”
Section: Two Experiments With the Capmentioning
confidence: 99%
“…1 Yaari (1965), Sheshinski (2008) and the other papers on which these arguments are based generally make two crucial assumptions about survival uncertainty. 2 First, individuals are risk neutral over the length of life. Second, individuals know the survival probabilities that they face as they plan for the future.…”
Section: Introductionmentioning
confidence: 99%
“…Brown, Kapteyn, Luttmer, and Mitchell (2016) review a number of factors that could reduce the demand for annuities relative to Yaari's full annuitization result. 2 Beyond survival uncertainty, Yaari made a variety of other assumptions such as expected utility maximization, intertemporally separable utility, actuarially fair annuities, and market completeness. These assumptions have been relaxed systematically by Davido¤, Brown, and Diamond (2005) among others.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the literature on Social Security's overall welfare consequences has traditionally evolved as a comparison of the benefits of its insurance effects, to its distortionary costs on household behavior. This literature has broadly concluded that under traditional preferences, the welfare gains from the insurance effects of Social Security are considerably smaller than its distortionary welfare losses (Auerbach and Kotlikoff, 1987;Bagchi, 2015), although some find overall welfare gains, especially when labor supply is inelastic (Hubbard and Judd, 1987;İmrohoroglu, Imrohoroglu and Joines, 1995). This literature, however, has typically ignored how Social Security might interact with a third type of risk: the risk related to one's health status.…”
Section: Introductionmentioning
confidence: 99%